A Production systems study on the Cut-Meat Division of Del Monte Philippines, Incorporated - Gonzales, Caryn O.; Jacildo, Mark Wendell B.; Moncada, Marchae Gizette B. (Diliman, Quezon City College of Engineering, 1996)
This paper is a study of the production and operations system of the Cut-Meat Division of Del Monte Philippines, Incorporated. The first part of the paper narrates a brief history of Del Monte and its Cut-Meat Division. Presented also are the company objectives, organizational structure, and the company's product line. A documentation of the existing production system then follows. The production system starts with the slaughtering process followed by carcass hanging and aging and then finally carcass withdrawal and pick-up. Facilities and equipment necessary for the operations are also identified. These are the APDC stockyard, cattle slaughtering area and the reefer vans/ The different forms used by the company is also presented as well as the workforce level that the company is presently employing. The company functions in product distribution, promotional activities, and forecasting are then discussed. Problems affecting the Cut-Meat Division's operations are identified. These are: in the Production Division, where under-utilization of facility is present; production distribution, where the company's dependence on its sole distributor together with the radius requirement o SM supermarkets prevent their expansion; and the systems and procedures part, where an inappropriate form is used. Alternative solutions to these problems are generated. These are ten compared with each other and then evaluated to come up with the best possible solution for the problems at hand. Finally, recommendations to eliminate the problem and further improve the existing system of Del Monte's Cut Meat Division are presented. These are the employment of 10 workers to meet expected demand and to maximize utilization of the facility they are using; assessment of the performance of Atilla, Incorporated in terms of generating contacts and distribution centers, review of the agreements between Atilla, Incorporated and its distribution centers to prevent radius requirement problems which hinder the expansion of Del Monte's product distribution; and the making of a form to use appropriately as receipt.
IE 151
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Del Monte Philippines Incorporated; Meat industry and trade; Production engineering